(untitled) (Journal of Advanced Research in Journalism & Mass Communication, 2018)
In the communication era India continues to be an agrarian society. 60% of the population does agriculture and allied works. In a land of such agriculture importance, news media hesitate to provide reports about agriculture and the agrarian crisis. India is one of the countries which have alarmingly increase number of farmer suicide. According to ‘National Crime record bureau’ nearly 31 lakhs farmers commit suicide over the past 20years. ‘Census of India’ statistics states that farmer’s population declines rapidly at the rate of 70 lakhs per year. Climate change, change in the government policy and many other factors play an important role in pushing the farmers to a pathetic plight. In this scenario the role of media is very important in educating the farmers about the latest development in the agriculture parlance and also informing the common public about the plight of the agrarians. Hence it is necessary to study the role of news papers in informing the public about the news related to agriculture which is the live wire of the Indian society. This research paper tries to analyze the framing technique adopted by the newspaper The Hindu (Tamil and English) in reporting the news about Tamilnadu farmers’s protest at Jantar Mantar, Delhi. The study applies Entman’s “Frame analysis” method to analyse the news about the“farmers protest at Jantar Mantar”. The news papers taken for analysis are “The Hindu” Tamil and “The Hindu” English, because both the newspapers are from the same house of publication but applies different news framing in reporting the news about “farmers protest at Jantar Mantar”. How to cite this article: Thalha MAJ, Prabha RR. Tamil Nadu farmers Protest at Jantar Mantar: News Frame Analysis. J Adv Res Jour Mass Comm 2018; 5(3): 40-47.